EFEKTIVITAS KONSELING KELOMPOK BEHAVIORAL TEKNIK EXTINCTION DALAM MEREDUKSI HIGHLY EMOTIONAL CHARACTER PADA SISWA KELAS VIII A SMP MUHAMMADIYAH 2 SURAKARTA TAHUN 2024/2025: penelitian eksperimen kuantitatif - Istiqomah, Istiqomah; Jawandi, Ahmad; Putro, Eko Adi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
A highly emotional character is a pattern of behavior that is unconsciously designed to warn intruders to stop threatening behavior towards oneself. Additionally, a highly emotional character is a psychological response to prevent disturbances before they occur or to address and retaliate after such disturbances have occurred. The research method used was an experiment with a one-group pretest-posttest design. The subjects of this study were seven eighth-grade students selected using purposive sampling. The instrument used in this study was a questionnaire designed to measure the level of highly emotional behavior in students before and after group counseling using the extinction technique. The data obtained was then analyzed using the Wilcoxon test, and H0 was rejected and Ha was accepted. The results of the study indicate that there was a significant decrease in the Highly Emotional Character behavior of students after participating in group counseling using the extinction technique. Therefore, it can be concluded that there was a difference in the mean between before and after the group counseling using the extinction technique was administered, which was effective in reducing the Highly Emotional Character behavior of students in class VIII A at SMP Muhammadiyah 2 Surakarta. This study is expected to contribute to the development of guidance and counseling programs in schools to foster more positive behavior among all students.